2014
DOI: 10.1038/jid.2013.278
|View full text |Cite
|
Sign up to set email alerts
|

RhoB Promotes Cancer Initiation by Protecting Keratinocytes from UVB-Induced Apoptosis but Limits Tumor Aggressiveness

Abstract: The role of UVB-induced apoptosis in the formation of squamous cell carcinoma (SCC) is recognized. We previously identified the small RhoB (Ras homolog gene family, member B) GTPase, an early response gene to cellular stress, as a critical protein controlling apoptosis of human keratinocytes after UVB exposure. Here we generated SKH1 (hairless immunocompetent mouse) mice invalidated for RhoB to evaluate its role in UVB-induced skin carcinogenesis in vivo. We show that rhob-/- mice have a lower risk of developi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…6). We recently reported that RhoB-deficient human skin tumors also have elevated ␥H2AX levels compared to RhoB-proficient tumors (63). Hence, our findings suggest that loss of RhoB could promote oncogenesis by increasing DSB-mediated genomic instability.…”
Section: Discussionmentioning
confidence: 53%
“…6). We recently reported that RhoB-deficient human skin tumors also have elevated ␥H2AX levels compared to RhoB-proficient tumors (63). Hence, our findings suggest that loss of RhoB could promote oncogenesis by increasing DSB-mediated genomic instability.…”
Section: Discussionmentioning
confidence: 53%
“…Therefore, correlation of experimental observations made in murine models and in human tissue is of prime importance for demonstrating relevance to human disease. Mouse models, most notably those employing the SKH-1 hairless immunocompetent mouse, proved to be useful and allowed the identification of critical molecular and biologic changes that trigger skin tumour development [[14], [15]]. They are also commonly used to assess the preclinical efficacy of novel treatments on SCC however, rather than on AK lesions [[10]; [9], [8], [16]].…”
Section: Discussionmentioning
confidence: 99%
“…For example, early studies revealed that ablation of the RhoB gene in mice (a gene deleted in many human cancers) enhances carcinogen-induced skin cancer (15). Rhob −/− mice are less prone to form squamous cell carcinomas following chronic exposure to UVB, arguing that RhoB favors early stages of oncogenesis, however RhoB could also limit the progression to highly aggressive tumors (16). Deletion of the RhoC gene in the MMTV-PyVT mouse model of breast cancer significantly reduces lung metastasis of mammary tumors (17).…”
Section: Distinctive Roles For Rho Gtpases In Cancer Initiation and Pmentioning
confidence: 99%